MATHEMATICS LESSON DEMONSTRATION: "AMD" METHOD AND ITS APPLICATION - Munkhtaria Khayankhyarvaa (International Journal of Innovative Technologies in Social Science, 2025)
A methodology was created and tested to design teaching materials for each subject that enhance children's engagement in math lessons, foster motivation and curiosity in learning math independently. This was achieved by converting study materials into educational activities rooted in the principles of mathematical anthropology, mathematics, and teaching methods, incorporating both theoretical and practical aspects.In today's education landscape, teaching aids, presentation materials, and handouts are essential tools for teachers to effectively engage students and facilitate active and participatory learning in the classroom. While traditional mathematics instruction focused primarily on memorizing facts, there is now a greater emphasis on applying facts in different contexts and developing proficiency in mathematical methods.Enhancing the importance of mathematical knowledge in general culture, broadening the objectives of mathematical education, enhancing and refining the quality of educational training, and enhancing the content, formats, and methodologies of organizing mathematical teaching materials. A fresh perspective is emerging on demonstration materials, with demonstration playing a crucial role in concept formation. Encouraging students' cognitive engagement, establishing a rapid "teacher-student" connection with personalized learning approaches, aiming to minimize unproductive time during lessons, and the practical integration of educational technology in all schools have greatly enhanced the methods of teaching mathematics.The successful implementation of the teacher's planned methodology hinges on the use of teaching materials. Teachers typically view materials as encompassing blackboards, chalk, handouts, presentations, and textbooks. However, materials also encompass motivational strategies and tasks integrated into the lesson content. By preparing additional materials at the conclusion of each regular lesson, students can effectively utilize the provided scenarios to deepen their understanding and knowledge. The teacher's proficiency in facilitating discussions, lectures, and demonstrations, as well as organizing students' investigative activities, plays a crucial role in enhancing students' cognitive engagement.